Moving Backgrounds Confer Age-Related Positional Uncertainty on Flash-Grab Targets. (September 2019) - Anstis, Stuart
The flash-grab effect made a stationary flashing cross appear to jump back and forth through a distance of more than 2°. Observers were asked to move a cursor as quickly as possible on to this flashing target. All observers younger than 65 years, and 39% of those over 65 years, could do this without difficulty within 1 second to 2 seconds. But 61% of those over 65 years experienced uncertainty about the exact position of the target and took from 6 to 147 seconds to hit it—about 4 times longer than to hit an actually jumping cross. This loss of hand–eye coordination was probably perceptual, not motor.